The new frontier of public health education. Issue 1 (6th February 2017) - Birnbaum, David; Gretsinger, Kathryn; Ellis, Ursula
Abstract : Purpose: The aim of this paper is to describe the experience and educational benefits of a course that has several unique educational design features. Design/methodology/approach: This includes narrative description of faculty and student experience from participants in a flipped-instructional-design inter-professional education course. Findings: "Improving Public Health – An Interprofessional Approach to Designing and Implementing Effective Interventions" is an undergraduate public health course open to students regardless of background. Its student activities mirror the real-life tasks and challenges of working in a public health agency, including team-building and leadership; problem and project definition and prioritization; evidence-finding and critical appraisal; written and oral presentation; and press interviews. Students successfully developed project proposals to address real problems in a wide range of communities and settings and refined those proposals through interaction with professionals from population and public health, journalism and library sciences. Practical implications: Undergraduate public health education is a relatively new endeavor, and experience with this new approach may be of value to other educators. Originality/value: Students in this course, journalism graduate students who conducted mock interviews with them and instructors who oversaw the course all describe unique aspects and related personal benefit from this novel approach.